Using participatory system dynamics modelling to quantify indirect land use changes of biofuel projects. Issue 1 (2nd January 2021) - Di Lucia, Lorenzo; Peterson, Steve; Sevigné-Itoiz, Eva; Atzori, Alberto; Usai, Domenico; Slade, Raphael; Bauen, Ausilio
ABSTRACT: The use of biomass to produce biofuels can lead to both direct and indirect Land Use Change (LUC). While the causes underlying LUCs are complex their quantification is a scientific challenge that hinders decision-making. Here we demonstrate the application of participatory modelling in combination with System Dynamics techniques to the analysis of the land-change dynamics associated with biofuel supply chains. The ambition is to provide decision-makers with useful and credible knowledge of direct and indirect LUCs. We illustrate the application of the approach by applying it to a real‐world project for the production of advanced biofuels in Sardinia (Italy). The results show that the land use displacements vary in intensity and persistence depending on the crop management regime applied and the future development of the market of sheep cheese. The results were considered credible by actors with direct knowledge of the 'real' system and useful by decision makers .